Automated Essay Scoring Feedback (AESF): An Innovative Writing Solution to the Malaysian University English Test (MUET) - Lee, Nung Kion; Ng, Sing Yii; Bong, Chih How; Hong, Kian Sam (International Journal of Teaching and Learning in Higher Education (IJTLHE), 2016)
Recent advances in information communication technology (ICT) infrastructure can be harnessed to support and improve the quality of teaching and learning of English writing skills especially for second language context where rule based support is necessary. Essay writing is indeed the most demanding task to both teachers and students. From conducting the class to assigning of task as well as marking and providing feedback by teachers whereas from drafting essays to final submission and resubmission of essays by students require on-going iterative cycles to facilitate improvement. However, a common scenario is that the iterative process takes too much time, thus resulting in limited practise. An innovative solution to imitate such process is via the Automated Essay Scoring Feedback (AESF). AESF is a networked tool that has the ability to score and provide feedback to students‟ essays instantaneously. With the speed that exceeds human ability and accuracy of a human scorer, it is hoped that AESF can increase the frequency of essay writing in the class that eventually result in improvement in students‟ performance. This paper aims to highlight the novelty and rationale of having AESF, its design and features as well as how this tool can be blended into the writing classroom, particularly for the Malaysian University English Test (MUET) extended essay writing.